IMPLEMENTASI NILAI PENDIDIKAN ISLAM MELALUI KEGIATAN MAJELIS TA’LIM NURUL FALAQ DALAM MENUMBUHKAN SIKAP GOTONG ROYONG PADA MASYARAKAT TALAGA RAYA - Linda, Linda Lestari; Basri; Abdul Rahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Majelis Ta'lim (Islamic study groups) as non-formal Islamic educational institutions play a strategic role in shaping the socio-religious attitudes of the community, including the value of mutual cooperation. However, empirical studies specifically examining the role of Majelis Ta'lim (Islamic study groups) in fostering mutual cooperation through religious activities are still relatively limited. This study aims to analyze the role of Majelis Ta'lim Nurul Falaq in fostering mutual cooperation and identify supporting and inhibiting factors in its implementation in Talaga Raya District, Central Buton Regency. This study used a qualitative method with a descriptive approach. Data collection techniques included semi-structured interviews, non-participatory observation, and documentation, with the research subjects consisting of the chairman and members of Majelis Ta'lim. Data analysis was carried out through the stages of data reduction, data presentation, and interactive conclusion drawing. The results of the study indicate that Majelis Ta'lim Nurul Falaq plays an active role in fostering mutual cooperation through routine religious activities, such as religious study groups, rotating Yasinan (recitation of the Yasinan), shalawatan (prayer), and social activities based on community awareness. These activities encourage the formation of values ​​of cooperation, solidarity, volunteerism, and social participation. The main supporting factors include congregational cohesion, participatory leadership, and social support, while time constraints and members' busy schedules are inhibiting factors. This study concludes that majelis ta'lim (Islamic study groups) significantly contribute to strengthening the value of mutual cooperation, thus contributing to strengthening social cohesion and developing the community's religious character.